Health Care Reform and human resources for health - García Cabrera, Hernán E. (2015)
The implementation of the Health Sector Reform in Peru, aims to improve the health status of residents in the country, recognizing that health is a fundamental right and that the State guarantees the protection of health for all persons without any discrimination at all stages of life; in this context, the Ministry of Health placed in the center of interventions addressing the problems in the field of human resources based on strategic planning, information system in human resources - National Register of Personal - INFORHUS, the methodological development of the estimation of gaps in health personnel and the development of strategies for recruitment and retention of staff, with priority for primary care, skills development in primary health care as management services and the health system, increase of seats SERUMS, Residentado, Internship, and the reactivation of the National School of Public Health. The Directorate General Management Human Resources Development chaired the Multisectoral Commission proposed the Comprehensive Compensation and Economic Delivery for health personnel in the public sector, approved by Legislative Decree 1153, which aims to reach the state greater equity, effectiveness, efficiency, and effectively deliver quality services in health to citizens.